The role of the queen in wax secretion and comb building in the Cape honeybee, Aps mellifera capensis (Escholtz) - Whiffler, Lynne Anne (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1992)
The role of the queen in wax secretion and comb building was studied in the the Cape honeybee, Apis mellifera capensis (Escholtz). The percentage of bees bearing wax and the amount of wax borne by these bees did not differ between the experiments. This meant that the queenless and queenright colonies had the potential to construct equal amounts of comb as the amounts of wax available for comb building was the same. Contrary to this prediction, queenright colonies constructed 8 times more comb than their queenless counterparts. Queenright Apis mellifera scutellata colonies constructed 4 times more comb than their queenless counterparts. The increased amount of 9-oxo-2-decanoic acid (90DA) in the A.m.capensis mandibular gland secretions could not alone account for this difference. In fact, A.m.capensis and A.m.scutellata colonies constructed similar amounts of comb when they were given their own queens or queens from the other race. Worker bees need to have direct contact with their queen for comb building to be enhanced. Even when the queen had her mandibular glands extirpated and tergite glands occluded large amounts of comb were constructed than when access to the queen was limited. Direct access to the head of a mated queen proved to be the stimulus enhancing comb building. No comb was constructed when the workers had access to the abdomen of the queen. Virgin queens did not stimulate comb building. The relatively large amounts of 90DA and 9HDA from the mandibular glands of Cape virgin queens had not influenced comb building. Worker sized cells were generally constructed. These cells were slightly smaller than those constructed by European honeybees, but were indicative of African bees. A few queen less colonies constructed cells that were of an intermediate drone and worker size. Four mandibular gland pneromones were measured by gas chromatography. No correlations between these pheromones and the comb construction measurements were found. It is unlikely that the mandibular gland pheromones are the only pheromones that stimulate comb building. Pheromones from other glands on the head may contribute towards the enhancement of comb building, and they are not present in virgin queens
Keywords: Honeybee; Honey, Comb; Beeswax; Bee culture -- Queen rearing